Kinetics study on non-isothermal crystallization of Ni1.5MnSn0.5Co alloy thin films. Issue 189 (4th May 2018) - Wang, Zhenhua; Guo, Erjun; Tan, Changlong; Tian, Xiaohua; Zhu, Jiachen; Zhao, Wenbin
ABSTRACT: The crystallization kinetics of the Ni1.5 MnSn0.5 Co free-standing alloy thin films is investigated by continuous heating differential scanning calorimetry (DSC). The results show that all the DSC traces have a single exothermic peak, with a long high temperature tail. The DSC curves have been analyzed in terms of activation energy and kinetic model. We find that the activation energy of film obtained by both the Kissinger and Ozawa equation methods can give consistent results, the activation energy for crystallization is determined as 221.2 and 220.9 KJ/ mol, respectively. Moreover, the volume fraction crystallized has significantly influence on the local activation energy, and the regular of the nucleation and growth of films has been changed at crystallization process. Our work would enrich the mechanism of the crystallization kinetics for annealing applications of Ni-Mn-Sn-Co thin films in microelectro mechanical systems (MEMS).